Stability analysis of hybrid Al2O- TiO2 nano-cutting fluids - Ariffin, Arifuddin; A. A.M., Redhwan; A. M., Syafiq; S., Zainal Ariffin; A. R.M., Aminullah; Wan Hamzah, Azmi (International OCSCO World Press, 2022)
Purpose: This paper is to study the stability of the current combination of hybrid nano-cutting fluids due to the recent progress in the analysis of nano-cutting fluids, such as the assessment methods for the stability of nano-cutting fluids, have revealed that instability is a common problem associated with nano cutting fluids. Design/methodology/approach: Five samples of 0.001 vol% that are suitable to be tested at UV-Vis machine, Al2O3–TiO2 hybrid nano-cutting fluid was prepared using a one-step process with the help of a magnetic stirrer to stir for 30 minutes with different sonication time to determine the best or optimum sonication time for this hybrid nano-cutting fluid. Stability of nano-cutting fluids was analyses using UV–Vis spectrophotometer (0.001%, 0.0001%, 0.00001%), visual sedimentation (1%, 2%, 3%, 4%), TEM photograph capturing techniques (2%) and zeta potential analysis (0.001%, 0.00001%), that used different volume concentration that is suitable for each type of stability analysis. Findings: The stability analysis reveals that the best sonication time is 90 minutes, and the UV-vis spectrophotometer shows the stability of all samples is above 80% during a month compared to the initial value. Further, visual sedimentation shows good stability with minimum sedimentation and colour separation only. The zeta potential value also shows great stability with a value of 37.6 mV. It is found that the hybrid nano-cutting fluid is stable for more than a month when the nano is suspended in the base fluid of conventional coolant. Research limitations/implications: The result in this paper is based on the experimental study of Al2O3-TiO2/CNC coolant base hybrid nano-cutting fluid for a month. However, to further validate the results presented in this paper, it is recommended to prolong the stability assessment time for six months for longer shelf life. Practical implications: The finding of this experimental study can be useful for high-precision product machining using similar CNC coolants, especially for aircraft and airspace applications for machining parts. Originality/value: No thorough stability assessment using all four types of stability analysis is done on Al2O3-TiO2/CNC Coolant base hybrid nano cutting fluid.